The moderating effect of independent board members' ownership on the relationship between their independence and firm performance - Omer Saeed Habtoor; Osama Hamad Alowaimer; Sami Sobhi Waked; Rayed Obaid Alobaid (Cogent Business & Management, 2024)
Despite the extensive research on the relationship between board independence and firm performance, which reveals an inconclusive result, there is a lack of evidence on the potential factors affecting this relationship. This study is an attempt to fill this gap by investigating whether equity ownership by independent board members affects the association between board independence and Saudi bank performance. To substantiate its hypotheses and sidestep endogeneity concerns, this study employs a panel dataset of Saudi listed banks from 2009 to 2018, using diverse statistical techniques, including feasible generalized least squares (FGLS), ordinary least squire (OLS), random-effects, panel-corrected standard errors (PCSE), fixed-effects, two-stage least squares (2SLS), two-step system generalized method of moments (GMM), and hierarchical analysis. The empirical results show that while independent board members have a negative impact on bank performance, their ownership has a positive influence. More interestingly, the results demonstrate that the negative relationship between bank financial and market performance and independent board members is positively and significantly moderated by their ownership. These findings challenge the notion that good governance practices like having more independent members on the board would lead to better firm performance and indicate that their effectiveness is contingent on their ownership level. Insights derived from agency theory and the convergence of interests hypothesis contribute valuable perspectives to this investigation and suggest that board independence would be efficient when the convergence of interests between independent board members and other shareholders is engaged.
Keywords: 650; Independent board members' ownership; bank performance; moderating effect; Saudi Arabia; panel data; instrumental variables; GMM